Analisis Asuhan Keperawatan pada Pasien dengan Kanker Serviks Stadium IV A di Ruang Irina D Atas RSUP Prof. DR. R. D. Kandou Manado - Karepowan, Stevany; Meo, Maria Lupita Nena; Toar, Juwita Moreen; Kundre, Rina (Mapalus Nursing Science Journal, 2025)
Background: Cervical cancer is one of the most frequently diagnosed causes of cervical cancer and the main cause of death in women. Based on data from the International Agency for Research on Cancer (IARC) GLOBOCAN, there were 396,914 new cancer cases and 234,511 deaths due to cancer in 2020. The complaint that emerged was pain. A non-pharmacological combination therapy that is effective in treating pain is lavender aromatherapy guided imagery therapy. Method: The case study used is descriptive, with data collection techniques through interviews, physical examination and observation. The lavender aromatherapy guided imagery therapy intervention was provided once a day for 10-15 minutes and carried out for 3 days. Pain scale measurement uses the Numeric Rating Scale (NRS). Results: the application of lavender aromatherapy guided imagery therapy to reduce pain resulted in a decrease in the pain scale before the intervention was obtained on a scale of 4 and after the intervention the pain was reduced on a scale of 2. Conclusion: Based on the results of the evaluation carried out, it was found that lavender aromatherapy guided imagery therapy was able to reduce pain in patients cervical cancer